Pengenalan Tentang Menjaga Hutan Untuk Menciptakan Masa Depan Hijau Melalui Kegiatan Penyuluhan di SMK Advent Sausapor Kabupaten Tambrauw - Descarlo Worabai; Matheus Beljai; Meliza S. Worabai; Evelin A. Tanur; Nunang L. May; Ana Tampang (I-Com: Indonesian Community Journal, 2024)
ABSTRACT Forests and humans have a mutually influential relationship, where forest sustainability is highly dependent on human awareness in managing and utilizing it wisely to support shared welfare. Forest conservation efforts require community participation, especially the younger generation, through outreach and education that can foster awareness and skills to maintain the sustainability of the ecological and economic functions of forests, such as those carried out at SMK Avent Sausapor. This outreach activity aims to educate students about the importance of forest conservation and the impact of forest damage on the environment, as well as encourage them to apply forest conservation practices in their daily lives. The method in this outreach uses lecture and discussion methods as one form of community education method. This outreach has succeeded in increasing participants' understanding of the importance of protecting forests and the environment. The evaluation results showed that 87,6% participants felt inspired and more aware of their responsibilities in preserving nature. Keywords: green future; outreach activities; protecting forests; and Tambrauw regency;